Contribution of Demographic Bonus and HDI to Regional Economic Growth: North Sumatra Perspective - Bambang Sutejo; Henny Purnawa Dewi; Andi; Muhammad Yusuf (Outline Publisher, 2025)
In Indonesia, economic growth can be encouraged through the demographic bonus. Therefore, this research aims to explore the influence of the demographic bonus (labor force and human development index) on the economic growth of North Sumatra. The research method used is quantitative research. The data used in this research is secondary data obtained from the Central Statistics Agency of North Sumatra Province 2001-2021. Data testing in this study was carried out using eviews-10.The research results show: 1) In the short term, the Labor Force variable has a negative and insignificant relationship with the rate of economic growth in North Sumatra Province in 2001-2021. 2) In the long term, the labor force variable has a positive and insignificant effect on the rate of economic growth in North Sumatra Province in 2001-2021. 3) In the short term, the HDI variable has a negative and insignificant relationship with the rate of economic growth in North Sumatra Province in 2001-2021. 40 In the long term, the HDI variable has a positive and insignificant effect on the rate of economic growth in North Sumatra Province in 2001-2021.